The Extended Superficial Musculoaponeurotic System Deep Plane Facelift - Hu, Shirley; Perkins, Stephen W. (Facial Plastic Surgery, 2022)
Over the past four decades, the senior author has evolved and perfected his preferred method for face and neck lifting, the extended superficial musculoaponeurotic system deep plane rhytidectomy, and submentoplasty. With this procedure, the superficial musculoaponeurotic system layer is addressed both in the face and neck, repositioning the tissues in a superior and posterior vector and creating a sling in the cervicomental area. Outcomes have proven to be both successful and long lasting. In this article, a detailed update and discussion of the specific techniques utilized are provided.
Keywords: facelift; rhytidectomy; platysmaplasty; deep plane; neck lift